Effect of Aegle Marmelos on Histopathological And Biochemical Changes In Isoproterenol Induced Myocardial Infarction In Rat - Muzammil, M. Syed; J, Sathish; Thirumagal, M.; Sabeen, M. Ayesha (Asian Journal of Pharmaceutical Research and Development, 2013)
From the very beginning of human existence, man has familiarized himself with medicinal plants and used them in a variety of ways throughout the ages. In view of the above considerations the present study was designed to investigate the effect of Aegle marmelos aqueous leaves extract on isoproterenol induced myocardial infarction and its phytochemical screening. In search of food and to cope successfully with human suffering, primitive man began to distinguish those plants suitable for nutritional purpose from others with definitive pharmacological action. The present investigation is part of continuing programme related to the phytochemical screening of Aegle marmelos (herbal extracts) and on Myocardial Infarction and their enhanced potential.